Imaging of cerebral aneurysms: a clinical perspective. Issue 1 (December 2016) - Yoon, Nam; McNally, Scott; Taussky, Philipp; Park, Min
Abstract Neuroimaging is a critical element in evaluating and treating patients with cerebral aneurysms. Each neuroimaging technique has unique strengths, weaknesses, and current developments. In this review, we discuss the utility of two primary noninvasive radiological techniques—computed tomography angiography (CTA) and magnetic resonance angiography (MRA)—as well as of digital subtraction angiography (DSA) for evaluation of cerebral aneurysms. These techniques allow comprehensive evaluation of aneurysm size, location, rupture status, and other imaging characteristics that guide clinicians to make appropriate and timely treatment recommendations.